2011
DOI: 10.1063/1.3552302
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced degradation in compensated p- and n-type Czochralski silicon wafers

Abstract: Light-induced degradation (LID) due to boron-oxygen complex formation seriously diminishes the minority carrier lifetime of p-type Czochralski-grown (Cz) wafers. Depending linearly on the boron concentration NA in uncompensated silicon, the boron-oxygen defect density was suggested to depend on the net doping concentration p0 = NA - ND in compensated p-type samples, containing similar amounts of boron and phosphorus [D. Macdonald, F. Rougieux, A. Cuevas, etal., Journal of Applied Physics 105, 093704 (2009)]. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Recent studies, however, found that the BO defect density was proportional in p-type Si to the net doping, rather than to the total B concentration, meaning that it could thus be reduced by compensation [2][3][4][5]. This finding was more recently contradicted by a study of the BOrelated light-induced degradation of compensated Si solar cells, of which the severity was found to depend on the total B concentration [6].…”
Section: Introductionmentioning
confidence: 48%
“…Recent studies, however, found that the BO defect density was proportional in p-type Si to the net doping, rather than to the total B concentration, meaning that it could thus be reduced by compensation [2][3][4][5]. This finding was more recently contradicted by a study of the BOrelated light-induced degradation of compensated Si solar cells, of which the severity was found to depend on the total B concentration [6].…”
Section: Introductionmentioning
confidence: 48%
“…Figure 1 shows the value of N Ã 1;total =½O i 2 as a function of the net doping concentration p 0 in all the degraded samples. The previous data obtained by Schmidt and Bothe 7 on B-doped wafers and those by Geilker et al 13 on compensated wafers are also plotted in Figure 1. One can see that all these normalized saturated effective defect densities increase linearly with an increase of p 0 , which is in good agreement with the previous reported studies.…”
mentioning
confidence: 79%
“…One can see that all these normalized saturated effective defect densities increase linearly with an increase of p 0 , which is in good agreement with the previous reported studies. [11][12][13] This linear relationship can be ascribed to the participation of positively charged O 2i stþ in our modified B s O 2i model that the LID arises from a latent center composed of a B s and a O 2i st0 . 18,19 The LID is indeed triggered by the fast-diffusion of O 2i stþ towards the B s through capturing an electron and utilizing the energy released during the electron-capture process.…”
mentioning
confidence: 98%
“…Nos anos de 1970, após a crise do petróleo, as células solares começaram a ser usadas em aplicações terrestres e o silício tipo p continuou a ser o padrão utilizado pela indústria. No entanto, demonstrou-se na última década que a dopagem com boro em todo o substrato pode produzir problemas de degradação da eficiência das células solares de uso terrestre, principalmente para lâminas normalmente usadas na indústria, que possuem resistividade da ordem de 1 Ω.cm [8,9]. Esta degradação é devida à interação entre os átomos de oxigênio presentes nas lâminas de silício cristalino Cz (Czochralski) com os átomos de boro, sendo que a radiação solar transforma os defeitos boro-oxigênio em centros de recombinação efetivos.…”
Section: Introductionunclassified